2017
DOI: 10.1186/s13569-017-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Two years survival of primary cardiac leiomyosarcoma managed by surgical and adjuvant therapy

Abstract: BackgroundCardiac tumors are a very rare entity. Leiomyosarcoma represents less than 1% of cases.Case presentationa 51-year-old woman diagnosed with primary left atrium leiomyosarcoma. She was treated by optimal surgery and adjuvant chemotherapy. She is still alive after a follow-up of 24 months without evidence of local or distant recurrence.ConclusionsCardiac leiomyosarcoma is a rare tumor with a dismal prognosis. Surgery is the mainstay of treatment. Adjuvant treatment is still controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In the literature, the optimal treatment approach regarding postoperative adjuvant therapy remains unclear: some studies found that the adjuvant approach failed to modify the natural course of the disease, 7 , 8 while others have demonstrated a better survival for patients whose surgery was followed by adjuvant chemotherapy. 6 , 9 …”
Section: Treatment Of Cardiac Sarcomasmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the optimal treatment approach regarding postoperative adjuvant therapy remains unclear: some studies found that the adjuvant approach failed to modify the natural course of the disease, 7 , 8 while others have demonstrated a better survival for patients whose surgery was followed by adjuvant chemotherapy. 6 , 9 …”
Section: Treatment Of Cardiac Sarcomasmentioning
confidence: 99%
“…In the literature, the optimal treatment approach regarding postoperative adjuvant therapy remains unclear: some studies found that the adjuvant approach failed to modify the natural course of the disease, 7,8 while others have demonstrated a better survival for patients whose surgery was followed by adjuvant chemotherapy. 6,9 Overall, anthracyclines (in particular, doxorubicin) and nitrogen mustard alkylating agents (in particular, ifosfamide), which represent the preferred chemotherapeutic choice to treat sarcomas originating from other sites, are the most common chemotherapy agents used also for cardiac sarcomas. However, the typical cardiotoxicity of anthracyclines should be kept in mind when adjuvant treatment is proposed to a patient.…”
Section: Treatment Of Cardiac Sarcomasmentioning
confidence: 99%
“…Other treatment regimens include combination of docetaxel and gemcitabine, and cyclophosphamide, vincristine, doxorubicin and dacarbazine 23. A very recent case of left atrial leiomyosarcoma in a 51-year-old patient was reported, who was also treated with surgery and six cycles of doxorubicin and ifosfamide and was found free of any recurrence after 2 years 25. We also gave  six cycles of doxorubicin and ifosfamide in adjuvant setting to our patient.…”
Section: Discussionmentioning
confidence: 83%
“…The unobstructed view from transesophageal echocardiography allows excellent visualization of structures not well seen on TTE, with a higher resolution [13]. CT scan and cardiac MRI may also provide further information about morphology, location, and extent of the mass [16].…”
Section: Discussionmentioning
confidence: 99%